SUBJECTIVE WELL-BEING DESCRIPTION OF SINGLE MOTHER WORKING IN LOVE PEACE VILLAGE HELVETIA - Lumongga; Sri Milfayetty; Suryani Hardjo (RADJA PUBLIKA, 2023)
Some of the things that are quite a problem for single mothers are taking care of their children alone, and at the same time they have to work to earn income to meet their daily needs. Even though being a single mother is very hard, they also have happiness as a single mother. This study aims to describe the subjective well-being of working single mothers. The research design is phenomenological. The number of respondents in this study were three people with three informants as a source of triangulation. Respondent data collection technique using purposive sampling. Research data was collected through observation and interviews. Data analysis techniques are carried out by means of data reduction, data display, and verification. The results of the study show that respondents can feel subjective well-being. For the subjective well-being aspect, the three respondents can also feel life satisfaction, because more positive affect appears. Internal factors are also very influential, so that respondents have a fairly high subjective well-being where the three respondents have a strong personality in living life, have the principle that they can definitely fight for their children, and have strong faith in God Almighty. Support from children, from family, and social support which are external factors also greatly affect the high subjective well-being of the three respondents. because more positive affect appears. Internal factors are also very influential, so that respondents have a fairly high subjective well-being where the three respondents have a strong personality in living life, have the principle that they can definitely fight for their children, and have strong faith in God Almighty. Support from children, from family, and social support which are external factors also greatly affect the high subjective well-being of the three respondents. because more positive affect appears. Internal factors are also very influential, so that respondents have a fairly high subjective well-being where the three respondents have a strong personality in living life, have the principle that they can definitely fight for their children, and have strong faith in God Almighty. Support from children, from family, and social support which are external factors also greatly affect the high subjective well-being of the three respondents. and have strong faith in God Almighty. Support from children, from family, and social support which are external factors also greatly affect the high subjective well-being of the three respondents. and have strong faith in God Almighty. Support from children, from family, and social support which are external factors also greatly affect the high subjective well-being of the three respondents.